Efficient and stable high-entropy alloy catalyst as well as preparation method and application thereof
The high-entropy alloy thin film catalyst such as CoNiTaRuMn is prepared through magnetron sputtering technology, and its electronic structure and active sites are optimized, which solves the problems of high cost and poor stability of platinum alternative catalysts in the prior art, and achieves efficient and stable electro-hydrogen analytical properties.
Patent Information
- Application Number
- CN202411978664.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to develop efficient and stable low-cost platinum alternative catalysts, especially in electrolytic hydrogen evolution reactions. The high cost and low abundance of precious metal catalysts limit their large-scale application.
Magneto-controlled sputtering technology is used to prepare high-entropy alloy thin film catalysts such as CoNiTaRuMn. By controlling the magnetron sputtering time and element molar ratio, the electronic structure and active sites of the catalyst are optimized.
It achieves a voltage of only 142mV at an industrial current density of 500mA cm-2 and can operate stably for more than 1000 hours, surpassing commercial Pt/C nanoparticles and most precious metal catalysts.
Smart Images

Figure CN119776882A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of HER electrocatalysis, specifically to an efficient and stable high entropy alloy catalyst and a preparation method and application thereof, and in particular to a CoNiTaRuMn high entropy alloy electronic structure nanomaterial regulated by transition metal Mn and a preparation method thereof. Background Art
[0002] Renewable energy-driven water electrolysis is a green, zero-carbon hydrogen production pathway. In the electrochemical hydrogen evolution reaction (HER), highly active and stable catalysts are critical to reducing the capital cost of H2. Among them, precious metal-based alloy electrocatalysts exhibit excellent HER performance, with platinum (Pt) being the most effective HER catalyst due to its high exchange current density, low Tafel slope, and excellent stability. However, the low abundance and high cost of Pt limit its large-scale commercial application. In order to reduce costs and improve the efficiency and industrialization of hydrogen production by electrohydrolysis, industry researchers must look for efficient, low-cost, and durable platinum alternative catalysts. A promising option is ruthenium (Ru)-based catalysts. Ru is an important catalytic active site for the HER reaction. It is less expensive than Pt and has high abundance, and is widely used in electrochemical applications.
[0003] In recent years, high entropy alloys (HEAs) have attracted wide attention in the field of electrocatalysis due to their unique properties. In particular, the multi-components in HEAs provide unique electronic structures and diverse surface active sites in the field of catalysis. Even more striking is that the components of HEAs are highly tunable, which provides great possibilities for adapting to different catalytic reactions.
[0004] However, the synthesis of efficient and highly stable catalysts remains very challenging due to the complexity of multicomponent HEAs and their interactions. Summary of the invention
[0005] The main purpose of the present invention is to provide an efficient and stable high entropy alloy catalyst and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0006] Another object of the present invention is to provide an application of the highly efficient and stable high entropy alloy catalyst.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0008] An embodiment of the present invention provides an efficient and stable high-entropy alloy catalyst, whose chemical formula includes a combination of at least any four of Co, Ni, Ta, Ru, and Mn, that is, at least any one of CoNiTaRuMn, CoNiTaRu, CoNiRuMn, CoTaRuMn, NiTaRuMn, and CoNiTaMn.
[0009] The embodiment of the present invention also provides a method for preparing an efficient and stable high entropy alloy catalyst, which comprises: using magnetron sputtering technology, using a metal target as a target material, and depositing a high entropy alloy film on the surface of a substrate, that is, a highly efficient and stable high entropy alloy catalyst;
[0010] The metal target includes a combination of at least any four of a Ta target, a Mn target, a Co target, a Ni target and a Ru target.
[0011] In some embodiments, the preparation method includes: placing the substrate and the metal target on the sample table and the evaporation source position in the cavity of the magnetron sputtering equipment, respectively, evacuating the cavity of the magnetron sputtering equipment, then introducing a protective gas to the working gas pressure, and applying power for sputtering to obtain the efficient and stable high entropy alloy catalyst.
[0012] The embodiment of the present invention also provides the use of the efficient and stable high entropy alloy catalyst in the hydrogen evolution reaction of water electrolysis.
[0013] Correspondingly, an embodiment of the present invention further provides a hydrogen evolution catalyst, which includes: the aforementioned efficient and stable high entropy alloy catalyst.
[0014] Compared with the prior art, the beneficial effects of the present invention are at least:
[0015] (1) The high entropy alloy thin film catalyst prepared by the magnetron sputtering method of the present invention has uniform thickness, and the thickness of the film can be controlled by controlling the magnetron sputtering time;
[0016] (2) The present invention found that the electronic interaction between Co, Ni, Ta and Mn and Ru promoted the conversion of Ru from an oxidized state to Ru 4+ The transformation of Mn, especially compared with other elements, has a more significant effect on optimizing the valence state transfer of Ru, resulting in a unique electronic structure, thereby improving the activity of the catalyst. The prepared high entropy alloy thin film catalyst exhibits excellent electrohydrolysis performance at 500 mA cm -2 It only requires 142 mV at an industrial current density and can operate stably for more than 1000 hours, surpassing commercial Pt / C nanoparticles and most precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1a and Figure 1b They are scanning electron microscope photographs of the high entropy alloy thin film catalyst prepared in Example 1 of the present invention at different magnifications;
[0019] Figure 2a and Figure 2b They are respectively a TEM image and a selected area electron diffraction (SAED) pattern diagram of the high entropy alloy CoNiTaRuMn thin film catalyst prepared in Example 1 of the present invention;
[0020] Figure 3 is the EDS elemental diagram of the high entropy alloy CoNiTaRuMn thin film catalyst prepared in Example 1 of the present invention;
[0021] Figure 4 The high entropy alloy CoNiTaRuMn thin film catalyst prepared in Example 1 of the present invention is 1000mA cm- 2 The stability test diagram below;
[0022] Figure 5 HER polarization curves of high entropy alloy thin film catalysts prepared in Examples 1-6 of the present invention and Comparative Example 1;
[0023] Figure 6 It is the Tafel slope graph of the high entropy alloy thin film catalyst prepared in Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0024] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution mainly combines the advantages of ruthenium-based catalysts and high-entropy alloys in providing diverse surface active sites, thereby reducing the content of precious metal Ru and developing a high-entropy alloy catalyst with low Ru, high activity and high stability at industrial-grade current density.
[0025] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Specifically, as one aspect of the technical solution of the present invention, the chemical formula of a high entropy alloy catalyst involved includes at least any one of CoNiTaRuMn, CoNiTaRu, CoNiRuMn, CoTaRuMn, NiTaRuMn, and CoNiTaMn.
[0027] In some embodiments, the high entropy alloy catalyst comprises a high entropy alloy thin film.
[0028] In some more preferred embodiments, the high entropy alloy catalyst includes at least any one of CoNiTaRuMn high entropy alloy film, CoNiTaRu high entropy alloy film, CoNiRuMn high entropy alloy film, CoTaRuMn high entropy alloy film, NiTaRuMn high entropy alloy film, CoNiTaMn high entropy alloy film, etc., preferably an alloy film containing Ru, specifically including at least any one of CoNiTaRuMn high entropy alloy film, CoNiTaRu high entropy alloy film, CoNiRuMn high entropy alloy film, CoTaRuMn high entropy alloy film, and NiTaRuMn high entropy alloy film, especially preferably CoNiTaRuMn high entropy alloy film.
[0029] In some embodiments, the thickness of the high entropy alloy film is 0.2 to 5 μm.
[0030] In some more preferred embodiments, the molar ratio of Co element, Ni element, Ta element, Ru element and Mn element in the CoNiTaRuMn high entropy alloy film is 0.1-3: 0.05-2: 0.1-1: 0.1-0.8: 0.2-3.
[0031] In some more preferred embodiments, the molar ratio of Co element, Ni element, Ta element and Ru element in the CoNiTaRu high entropy alloy film is 0.1-3: 0.05-2: 0.1-1: 0.1-0.8.
[0032] In some more preferred embodiments, the molar ratio of Co element, Ni element, Ru element and Mn element in the CoNiRuMn high entropy alloy film is 0.1-3: 0.05-2: 0.1-0.8: 0.2-3.
[0033] In some more preferred embodiments, the molar ratio of Co element, Ta element, Ru element and Mn element in the CoTaRuMn high entropy alloy film is 0.1-3:0.1-1:0.1-0.8:0.2-3.
[0034] In some more preferred embodiments, the molar ratio of Ni element, Ta element, Ru element and Mn element in the NiTaRuMn high entropy alloy film is 0.05-2: 0.1-1: 0.1-0.8: 0.2-3.
[0035] In some more preferred embodiments, the molar ratio of Co element, Ni element, Ta element and Mn element in the CoNiTaMn high entropy alloy film is 0.1-3: 0.05-2: 0.1-1: 0.2-3.
[0036] As another aspect of the technical solution of the present invention, a method for preparing an efficient and stable high-entropy alloy catalyst involves: using magnetron sputtering technology, taking a metal target as a target material, and depositing a high-entropy alloy film on the surface of a substrate, that is, a highly efficient and stable high-entropy alloy catalyst.
[0037] In some embodiments, the metal target includes a combination of at least any four metal target materials such as a Ta target, a Mn target, a Co target, a Ni target, and a Ru target.
[0038] In some embodiments, the preparation method includes: using magnetron sputtering technology to bombard a metal target with an inert gas in a vacuum environment, and depositing a layer of ultra-thin high-entropy alloy film with uniform distribution on a substrate after condensation and aggregation, to obtain a high-entropy alloy hydrogen evolution catalyst with good stability and excellent HER performance.
[0039] In some preferred embodiments, the preparation method specifically includes: placing the substrate and the metal target on the sample table and the evaporation source position in the cavity of the magnetron sputtering equipment respectively, evacuating the cavity of the magnetron sputtering equipment, then introducing a protective gas to the working gas pressure, and applying power for sputtering to obtain the efficient and stable high entropy alloy catalyst.
[0040] In some preferred embodiments, the vacuum degree in the chamber of the magnetron sputtering device is less than 1.0×10 -3 Pa, the volume flow rate of the protective gas introduced is 10-50 sccm, and the working gas pressure is 0.5-2 Pa.
[0041] Further, the protective gas includes argon gas, preferably pure argon gas with a purity of 99.9999%, but not limited thereto.
[0042] In some preferred embodiments, the preparation method includes: sputtering Co, Ni, Ru, Ta and Mn etc. with a DC power supply, and the sputtering time is 90N120min. The longer the sputtering time, the thicker the high entropy alloy film.
[0043] In some embodiments, the operating powers of the Co target, Ni target, Ru target, Ta target, and Mn target are all 40-200W.
[0044] Furthermore, the thickness of the high entropy alloy thin film catalyst prepared by the magnetron sputtering method of the present invention is uniform, and the thickness of the film can be controlled by controlling the magnetron sputtering time.
[0045] In some preferred embodiments, the preparation method further comprises: before the sputtering begins, + The metal target is cleaned by bombardment, wherein Ar + The time for bombarding the target is 5 to 30 minutes.
[0046] In some preferred embodiments, the substrate may include any one of carbon cloth, molybdenum mesh, nickel foam, copper foam, glassy carbon sheet, gold sheet, etc., but is not limited thereto.
[0047] In some preferred embodiments, the preparation method further comprises: first cleaning the substrate, and then placing the substrate on a sample stage in the chamber of the magnetron sputtering device.
[0048] Furthermore, the present invention adopts an acid pickling method to clean the substrate. Specifically, the cleaning method includes: in a protective atmosphere, soaking the substrate in concentrated nitric acid at 50°C to 150°C for 0.5 to 4 hours, then washing with water until neutral, then soaking in ethanol or acetone and ultrasonically cleaning for 5 to 90 minutes, and finally drying in a vacuum drying oven at 30°C to 80°C for 5 to 17 hours.
[0049] Among them, in some more specific embodiments, the preparation method of the efficient and stable high entropy alloy catalyst specifically includes the following steps:
[0050] According to the principle of magnetron sputtering, the cleaned and dried substrate and metal target are placed on the sample stage and evaporation source position in the chamber of the magnetron sputtering equipment respectively; the vacuum chamber is evacuated and then filled with argon as a protective atmosphere until the working pressure is reached; Ar + The target material is cleaned by bombardment to remove the surface oxide layer; sputtering begins, and finally a high entropy alloy thin film catalyst is obtained.
[0051] Furthermore, the substrate cleaning method is acid pickling, first soaking the substrate in concentrated nitric acid at 50°C to 150°C in an argon atmosphere for 0.5 to 4 hours, then rinsing with deionized water until neutral, then soaking in anhydrous ethanol and ultrasonically cleaning for 5 to 90 minutes, and finally drying in a vacuum drying oven for use.
[0052] As another aspect of the technical solution of the present invention, the efficient and stable high entropy alloy catalyst prepared by the present invention has excellent and stable electrocatalytic hydrogen evolution performance and can be applied to hydrogen evolution reaction in water electrolysis.
[0053] Furthermore, another aspect of an embodiment of the present invention provides a hydrogen evolution catalyst, which includes the aforementioned efficient and stable high entropy alloy catalyst.
[0054] Specifically, the high entropy alloy hydrogen evolution catalyst of the present invention exhibits excellent electrohydrolysis performance at 500 mA cm -2 It only requires 142mV voltage at the industrial current density and can operate stably for more than 1000 hours.
[0055] Furthermore, the high entropy alloy hydrogen evolution catalyst of the present invention has a high -2 The overpotential is 198 mV at an industrial current density and 1000 mA cm- 2 The catalytic activity can be maintained stably for more than 1000 hours at a constant current density, and the catalytic performance far exceeds that of commercial catalysts Pt / C nanoparticles and most precious metal catalysts.
[0056] Moreover, the preparation method of the present invention greatly reduces the dependence on precious metals, and the operation is controllable, the raw materials and substrates are easy to obtain, the cost is low, and the catalytic performance of the high entropy alloy film can be significantly improved.
[0057] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0058] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0059] Example 1
[0060] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 100°C in an argon atmosphere for 2 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 20 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 60°C for 10 hours for use.
[0061] The magnetron sputtering technology was used to place carbon in the reaction chamber, and Co, Ni, Ru, Ta, and Mn were sputtered using a DC power supply with a vacuum degree better than 1.0×10 -3Pa environment, the argon volume flow rate is 30sccm, and the working pressure is 2Pa. Ar is used to bombard the target for 20min, and then condensed and gathered to deposit CoNiTaRuMn high entropy alloy film on carbon cloth; the working power of Co target is 44W, the working power of Ni target is 44W, the working power of Ru target is 56W, the working power of Ta target is 120W, the working power of Mn target is 120W, the deposition thickness is 1μm, and the sputtering time is 105min.
[0062] The high entropy alloy thin film catalyst with high catalytic performance prepared in this example was characterized.
[0063] See also Figure 1a , Figure 1b , Figure 2a , Figure 2b , Figure 3 and Figure 4 , are the scanning electron microscope images, transmission electron microscope images, TEM EDS images and the 1000mA cm- 2 The following stability test diagram. From the above diagrams, we can see that Figure 1a and Figure 1b It was demonstrated that the CoNiTaRuMn high entropy alloy film formed a smooth columnar structure supported on carbon fiber, with a cross-sectional thickness of up to 1μm. Figure 2a and Figure 2b High-resolution transmission electron microscopy (HRTEM) images and selected area electron diffraction (SAED) patterns of CoNiTaRuMn are shown. No lattice fringes are observed in the HRTEM images, while the SAED pattern shows diffuse halos, indicating that the CoNiTaRuMn catalyst has amorphous characteristics. Figure 3 ,The scanning EDS image shows that the five alloy elements of CoNiTaRuMn are evenly distributed without segregation. Figure 4 The CoNiTaRuMn high entropy alloy catalyst was shown to operate continuously for more than 1000 hours without attenuation, meeting the needs of industrial electrocatalysis. Figure 5 and Figure 6 As shown in the figure, according to the HER catalytic performance test results, at 500 mA cm 2 At the current density, the overpotential is 142mV and the Tafel slope is 17.16mV dec- 1 .
[0064] Comparative Example 1
[0065] The present invention selects the currently commercially available catalyst Pt / C as the HER benchmark catalyst and as a comparative sample. The preparation method is as follows: 5 mg of Pt / C catalyst powder is dispersed in 1 mL of Nafion ethanol solution, and the Nafion ethanol solution is prepared by 980 μL of ethanol and 20 μL of 5% Nafion solution. The obtained suspension is soaked in an ultrasonic bath for 1 hour until a uniform mixture is formed. Subsequently, 36 μL of the suspension is dripped onto a carbon fiber cloth (6×6 mm 2 ) with a loading mass of approximately 0.50 mg cm -2 , dried at 25°C. According to the HER catalytic performance test results, at 500mA cm- 2 At this current density, the overpotential is 170 mV.
[0066] Example 2
[0067] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 100°C in an argon atmosphere for 2 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 20 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 60°C for 10 hours for use.
[0068] The magnetron sputtering technology was used to place carbon in the reaction chamber, and Co, Ni, Ru and Mn targets were used as targets. A DC power supply was used to sputter Co, Ni, Ru and Mn. -3 Pa environment, the argon volume flow rate is 30sccm, and the working pressure is 2Pa. Ar is used to bombard the target for 20min, and then condensed and aggregated to deposit CoNiRuMn high entropy alloy film on carbon cloth; the working power of Co target is 44W, the working power of Ni target is 44W, the working power of Ru target is 56W, the working power of Mn target is 120W, the deposition thickness is 1μm, and the sputtering time is 2h.
[0069] The high entropy alloy thin film catalyst with high catalytic performance prepared in this example was characterized.
[0070] like Figure 5 and Figure 6 As shown, according to the HER catalytic performance test results, at 500mA cm- 2 At the current density, the overpotential is 151 mV and the Tafel slope is 26.48 mV dec.
[0071] Example 3
[0072] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 100°C in an argon atmosphere for 2 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 20 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 60°C for 10 hours for use.
[0073] The magnetron sputtering technology was used to place carbon in the reaction chamber, and Co, Ni, Ru and Ru targets were used as targets. A DC power supply was used to sputter Co, Ni, Ru and Ta. -3 Pa environment, the argon volume flow rate is 30sccm, and the working pressure is 2Pa. Ar is used to bombard the target for 20min, and then condensed and gathered to form a CoNiTaRu high entropy alloy film on the carbon cloth; the working power of the Co target is 44W, the working power of the Ni target is 44W, the working power of the Ru target is 56W, the working power of the Ta target is 120W, the deposition thickness is 1μm, and the sputtering time is 2h.
[0074] The high entropy alloy thin film catalyst with high catalytic performance prepared in this example was characterized.
[0075] like Figure 5 and Figure 6 As shown, according to the HER catalytic performance test results, at 500mA cm- 2 At this current density, the overpotential is 220 mV and the Tafel slope is 30.78 mV dec.
[0076] Example 4
[0077] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 100°C in an argon atmosphere for 2 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 20 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 30°C for 17 hours for use.
[0078] The magnetron sputtering technology was used to place carbon in the reaction chamber, and Co, Ta, Ru, and Mn targets were used as targets. A DC power supply was used to sputter Co, Ta, Ru, and Mn. -3 Pa environment, the argon volume flow rate is 30sccm, and the working pressure is 2Pa. Ar is used to bombard the target for 20min, and then condensed and aggregated to deposit CoTaRuMn high entropy alloy film on carbon cloth; the working power of Co target is 44W, the working power of Ta target is 120W, the working power of Ru target is 56W, the working power of Mn target is 120W, the deposition thickness is 1μm, and the sputtering time is 2h.
[0079] The high entropy alloy thin film catalyst with high catalytic performance prepared in this example was characterized.
[0080] like Figure 5 and Figure 6 As shown, according to the HER catalytic performance test results, at 500mA cm- 2At the current density, the overpotential is 147 mV and the Tafel slope is 29.04 mV dec.
[0081] Example 5
[0082] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 100°C in an argon atmosphere for 2 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 20 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 80°C for 5 hours for use.
[0083] The magnetron sputtering technology is used to arrange carbon in the reaction chamber, and Ni, Ta, Ru and Mn targets are used as targets. A DC power supply is used to sputter Ni, Ta, Ru and Mn. -3 Pa environment, the argon volume flow rate is 30sccm, and the working pressure is 2Pa. Ar is used to bombard the target for 20min, and then condensed and aggregated to deposit NiTaRuMn high entropy alloy film on carbon cloth; the working power of Ni target is 44W, the working power of Ta target is 120W, the working power of Ru target is 56W, the working power of Mn target is 120W, the deposition thickness is 1μm, and the sputtering time is 2h.
[0084] The high entropy alloy thin film catalyst with high catalytic performance prepared in this example was characterized.
[0085] like Figure 5 and Figure 6 As shown in the figure, according to the HER catalytic performance test results, at 500 mA cm -2 At the current density, the overpotential is 131mV and the Tafel slope is 28mV dec -1 .
[0086] Example 6
[0087] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 100°C in an argon atmosphere for 2 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 20 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 50°C for 12 hours for use.
[0088] The magnetron sputtering technology is used to place carbon in the reaction chamber, and Co, Ni, Ta and Mn are sputtered using a DC power supply with a vacuum degree better than 1.0×10 -3Pa environment, the argon volume flow rate is 30sccm, and the working pressure is 2Pa. Ar is used to bombard the target for 20min, and then condensed and gathered to form a CoNiTaMn high entropy alloy film on the carbon cloth; the working power of the Co target is 44W, the working power of the Ni target is 44W, the working power of the Ta target is 120W, and the working power of the Mn target is 120W. The deposition thickness is 1μm and the sputtering time is 2h.
[0089] The high entropy alloy thin film catalyst with high catalytic performance prepared in this example was characterized.
[0090] like Figure 5 and Figure 6 As shown in the figure, according to the HER catalytic performance test results, at 500 mA cm -2 At the current density, the overpotential is 292mV and the Tafel slope is 60.52mV dec -1 .
[0091] Example 7
[0092] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 50°C in an argon atmosphere for 4 hours, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 5 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 30°C for 17 hours for use.
[0093] The magnetron sputtering technology was used to place carbon in the reaction chamber, and Co, Ni, Ru, Ta, and Mn were sputtered using a DC power supply with a vacuum degree better than 1.0×10 -3 Pa environment, the argon volume flow rate is 10sccm, and the working pressure is 1.5Pa. Ar is used to bombard the target for 5min, and then condensed and gathered to form a CoNiTaRuMn high entropy alloy film on the carbon cloth; the working power of the Co target is 44W, the working power of the Ni target is 44W, the working power of the Ru target is 56W, the working power of the Ta target is 120W, and the working power of the Mn target is 120W. The deposition thickness is 1μm and the sputtering time is 90min.
[0094] Example 8
[0095] The carbon cloth substrate was acid-washed, first immersed in concentrated nitric acid at 150°C in an argon atmosphere for 0.5 hour, then rinsed with deionized water until neutral, then immersed in anhydrous ethanol for 90 minutes for ultrasonic cleaning, and finally dried in a vacuum drying oven at 80°C for 5 hours for use.
[0096] The magnetron sputtering technology is used to place carbon in the reaction chamber, and Co, Ni, Ta and Mn are sputtered using a DC power supply with a vacuum degree better than 1.0×10 -3 Pa environment, the argon volume flow rate is 50sccm, and the working pressure is 0.5Pa. Ar is used to bombard the target for 30min, and then condensed and gathered to form a CoNiTaMn high entropy alloy film on the carbon cloth; the working power of the Co target is 40W, the working power of the Ni target is 40W, the working power of the Ta target is 200W, the working power of the Mn target is 200W, the deposition thickness is 1μm, and the sputtering time is 2h.
[0097] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0098] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. An efficient and stable high entropy alloy catalyst, characterized in that: The chemical formula of the high entropy alloy catalyst includes a combination of at least any four of Co, Ni, Ta, Ru, and Mn.
2. The efficient and stable high entropy alloy catalyst according to claim 1, characterized in that: The high entropy alloy catalyst comprises a high entropy alloy film; preferably, the high entropy alloy catalyst comprises at least any one of a CoNiTaRuMn high entropy alloy film, a CoNiTaRu high entropy alloy film, a CoNiRuMn high entropy alloy film, a CoTaRuMn high entropy alloy film, a NiTaRuMn high entropy alloy film, and a CoNiTaMn high entropy alloy film, preferably comprises at least any one of a CoNiTaRuMn high entropy alloy film, a CoNiTaRu high entropy alloy film, a CoNiRuMn high entropy alloy film, a CoTaRuMn high entropy alloy film, and a NiTaRuMn high entropy alloy film, and is particularly preferably a CoNiTaRuMn high entropy alloy film; Preferably, the thickness of the high entropy alloy film is 0.2-5 μm.
3. The efficient and stable high entropy alloy catalyst according to claim 2, characterized in that: The molar ratio of Co element, Ni element, Ta element, Ru element and Mn element in the CoNiTaRuMn high entropy alloy film is 0.1-3: 0.05-2: 0.1-1: 0.1-0.8: 0.2-3; And / or, the molar ratio of Co element, Ni element, Ta element and Ru element in the CoNiTaRu high entropy alloy film is 0.1-3: 0.05-2: 0.1-1: 0.1-0.8; And / or, the molar ratio of Co element, Ni element, Ru element and Mn element in the CoNiRuMn high entropy alloy film is 0.1-3: 0.05-2: 0.1-0.8: 0.2-3; And / or, the molar ratio of Co element, Ta element, Ru element and Mn element in the CoTaRuMn high entropy alloy film is 0.1-3:0.1-1:0.1-0.8:0.2-3; And / or, the molar ratio of Ni element, Ta element, Ru element and Mn element in the NiTaRuMn high entropy alloy film is 0.05-2: 0.1-1: 0.1-0.8: 0.2-3; And / or, the molar ratio of Co element, Ni element, Ta element and Mn element in the CoNiTaMn high entropy alloy film is 0.1-3:0.05-2:0.1-1:0.2-3.
4. The method for preparing an efficient and stable high entropy alloy catalyst according to any one of claims 1 to 3, characterized in that: include: Using magnetron sputtering technology, with a metal target as the target material, a high entropy alloy film is deposited on the surface of the substrate, i.e., an efficient and stable high entropy alloy catalyst; The metal target includes a combination of at least any four of a Ta target, a Mn target, a Co target, a Ni target and a Ru target.
5. The preparation method according to claim 4, characterized in that: include: The substrate and the metal target are placed on the sample stage and the evaporation source position in the cavity of the magnetron sputtering device respectively, the cavity of the magnetron sputtering device is evacuated, and then a protective gas is introduced to the working gas pressure, and power is turned on for sputtering to obtain the efficient and stable high entropy alloy catalyst.
6. The preparation method according to claim 5, characterized in that: The vacuum degree in the cavity of the magnetron sputtering equipment is less than 1.0×10 -3 Pa, the volume flow rate of the protective gas introduced is 10-50 sccm, and the working gas pressure is 0.5-2 Pa; And / or, the protective gas includes argon.
7. The preparation method according to claim 5, characterized in that: include: Sputtering was performed using a DC power supply, with a sputtering time of 90 to 120 minutes; And / or, the operating power of the Co target, Ni target, Ru target, Ta target and Mn target is 40-200W.
8. The preparation method according to claim 6, characterized in that Also includes: Before sputtering begins, use Ar + The metal target is cleaned by bombardment, wherein Ar + The time for bombarding the target is 5 to 30 minutes; And / or, the substrate includes any one of carbon cloth, molybdenum mesh, nickel foam, copper foam, glassy carbon sheet, and gold sheet; And / or, the preparation method further includes: first cleaning the substrate, and then placing it on a sample table in the chamber of the magnetron sputtering equipment. Preferably, the substrate is cleaned by an acid pickling method. Particularly preferably, the cleaning method includes: in a protective atmosphere, soaking the substrate in concentrated nitric acid at 50°C to 150°C for 0.5 to 4 hours, then washing with water until neutral, then soaking in ethanol or acetone and ultrasonically cleaning for 5 to 90 minutes, and finally drying at 30°C to 80°C for 5 to 17 hours.
9. Use of the efficient and stable high entropy alloy catalyst according to any one of claims 1 to 3 in hydrogen evolution reaction by electrolysis of water.
10. A hydrogen evolution catalyst, characterized in that include: The efficient and stable high entropy alloy catalyst according to any one of claims 1 to 3.